The snail and the whale - Donaldson, Julia; Scheffler, Axel (New York : Dial Books for Young Readers, 2004)
Wanting to sail beyond its rock, a tiny snail hitches a ride on a big humpback whale and then is able to help the whale when it gets stuck in the sand.
Keywords: Snails -- Fiction; Whales -- Fiction; Stories in rhyme